2021
DOI: 10.1029/2021jg006430
|View full text |Cite
|
Sign up to set email alerts
|

Stable Carbon Isotope Depletions in Lipid Biomarkers Suggest Subsurface Carbon Fixation in Lava Caves

Abstract: Subsurface microbial communities are found across a range of depths on Earth, spanning shallow environments such as caves and aquifers 1-100 m deep (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 79 publications
(134 reference statements)
0
8
0
Order By: Relevance
“…may contribute to the differences in bacteria present inside of the caves from north to south; however, there was a large overlap in the major abundances found. A recent study (Selensky et al., 2021) suggests that surface environment is not a major factor in organic nutrient cycling in lava tubes, which further exemplifies them as isolated environments that may harbor chemolithoautotrophic organisms and biosignatures that are useful in the search for life in extraterrestrial lava tubes. Furthermore, Northup et al.…”
Section: Discussionmentioning
confidence: 99%
“…may contribute to the differences in bacteria present inside of the caves from north to south; however, there was a large overlap in the major abundances found. A recent study (Selensky et al., 2021) suggests that surface environment is not a major factor in organic nutrient cycling in lava tubes, which further exemplifies them as isolated environments that may harbor chemolithoautotrophic organisms and biosignatures that are useful in the search for life in extraterrestrial lava tubes. Furthermore, Northup et al.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding life potential, recent terrestrial studies revealed that subsurface geological settings provide the most diverse ecosystems—often dominated by chemolithotrophs and novel microbial lifeforms with significant implications for the origin and evolution of life on Earth (Escudero et al., 2020 ; Magnabosco et al., 2018 ; Miller et al., 2020 ; Selensky et al., 2021 ). These microorganisms play vital roles in almost all biological processes, such as global biogeochemical cycling, biomineralization, and pedogenesis (Gaboyer et al., 2017 ; Miller et al., 2018 ; Tornos et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…may contribute to the differences in bacteria present inside of the caves from north to south; however, there was a large overlap in the major abundances found. A recent study (Selensky et al, 2021) suggests that surface environment is not a major factor in organic nutrient cycling in lava tubes, which further exemplifies them as isolated environments that may harbor chemolithoautotrophic organisms and biosignatures that are useful in the search for life in extraterrestrial lava tubes. Furthermore, Northup et al (2016) found that bacterial diversity in Icelandic lava tubes differed substantially from that in surface soil samples, with the most abundant cave phylum being Actinobacteria, followed by Acidobacteria and Proteobacteria.…”
Section: Bacterial Communities Inhabiting Blue Mineral Precipitatesmentioning
confidence: 98%